REDISTRIBUTION OF FUNCTIONS AND POWERS BETWEEN LOCAL AND SUBREGIONAL LEVELS OF GOVERNANCE WHEN FORMING ENLARGED DISTRICTS - Barynova, Diana; Nesterenko , Viktor (Pressing Problems of Public Administration, 2021)
The article covers the issue of effectiveness of the distribution of functions and powers between the subjects of subregional and basic levels of governance in the context of decentralization, local government reform and territorial organization of power in Ukraine. The activity of executive bodies and local governments of the basic and district levels is analyzed using the example of the work of Kolomatskyi village council, Kolomatskyi district council and Kolomatskyi district state administration of Kharkiv region in terms of decentralization practices in 2017-2020. It was concluded that most of the powers and functions that belonged to the subregional level before the reform should be transferred to the basic level of administrative-territorial organization (community level); while at the subregional level, only the power to oversee the legality of decisions taken by local governments of the basic level should be left to provide the legal support of their activities, and coordination of territorial divisions of CEBs. In April 2020, the Cabinet of Ministers of Ukraine approved with its ordinance the administrative centers and territories of territorial communities, which formed the basis of the new administrative and territorial structure of Ukraine. In June 2020, the Resolution of the Verkhovna Rada of Ukraine liquidated the old districts and approved the number and configurations of the new ones. According to the referred documents, the new administrative and territorial structure consists of 1469 territorial communities and 136 enlarged districts. However, the issue of an effective separation of powers between the basic and subregional levels of governance has become even more relevant. The question of the continued existence of district councils on the eve of the local elections is very acute. Therefore, in the absence of amendments to the Constitution of Ukraine and other laws, after the elections to the new district councils in 2020, there are risks of an artificial strengthening of district councils in the coming years and the possibility of interference in the activity of the newly formed territorial communities due to ‘pulling-over’ the powers of administering communal property (schools, hospitals, utilities) for at least another five years – until the next local elections.